Child Caries Management: A Randomized Controlled Trial in Dental Practice. (January 2020) - Innes, N.P.; Clarkson, J.E.; Douglas, G.V.A.; Ryan, V.; Wilson, N.; Homer, T.; Marshman, Z.; McColl, E.; Vale, L.; Robertson, M.; Abouhajar, A.; Holmes, R.D.; et al.
This multicenter 3-arm, parallel-group, patient-randomized controlled trial compared clinical effectiveness of 3 treatment strategies over 3 y for managing dental caries in primary teeth in UK primary dental care. Participants aged 3 to 7 y with at least 1 primary molar with dentinal carious lesion were randomized across 3 arms (1:1:1 via centrally administered system with variable-length random permuted blocks): C+P, conventional carious lesion management (complete carious tooth tissue removal and restoration placement) with prevention; B+P, biological management (sealing in carious tooth tissue restoratively) with prevention; and PA, prevention alone (diet, plaque removal, fluorides, and fissure sealants). Parents, children, and dentists were not blind to allocated arm. Co–primary outcomes were 1) the proportion of participants with at least 1 episode of dental pain and/or infection and 2) the number of episodes of dental pain and/or infection during follow-up (minimum, 23 mo). In sum, 1, 144 participants were randomized (C+P, n = 386; B+P, n = 381; PA, n = 377) by 72 general dental practitioners, of whom 1, 058 (C+P, n = 352; B+P, n = 352; PA, n = 354) attended at least 1 study visit and were included in the primary analysis. The median follow-up was 33.8 mo (interquartile range, 23.8 to 36.7). Proportions of participants with at least 1 episode of dental pain and/or infection were as follows: C+P, 42%; B+P, 40%; PA, 45%. There was no evidence of a difference in incidence of dental pain and/or infection when B+P (adjusted risk difference [97.5% CI]: −2% [−10% to 6%]) or PA (4% [−4% to 12%]) was compared with C+P. The mean (SD) number of episodes of dental pain and/or infection were as follows: C+P, 0.62 (0.95); B+P, 0.58 (0.87); and PA, 0.72 (0.98). Superiority could not be concluded for number of episodes between B+P (adjusted incident rate ratio (97.5% CI): 0.95 [0.75 to 1.21]) or PA (1.18 [0.94 to 1.48]) and C+P. In conclusion, there was no evidence of a difference among the 3 treatment approaches for incidence or number of episodes of dental pain and/or infection experienced by these participants with high caries risk and established disease (trial registration: ISRCTN77044005).